Criminal justice system: a framework for reforms - Sankaran, S.R. (1999)
In the present scenario of the criminal justice system in the country, arrests run into millions, the jails are overcrowded mostly with undertrials and the courts are overstretched with several lakhs of pending criminal cases. Added to these are illegal detentions and extra-judicial killings as well as deaths in police and jail custody. Systemic reforms from a people-centred point of view are long overdue. Institutions like the National Human Rights Commission and the Supreme Court have to take the initiative in the matter as neither the state governments nor the central government seem to be interested in meaningful reforms. - Reproduced
Keywords: Jails - India; Crime - India; Administration of justice - India; Administration of justice